Literatur Review: Kajian Evolusi Paus Balin Secara Filogenetik dan Molekuler - Na’illah Ega Sivana; Rahajeng Galuh Tribuana; Rifqi Ilham; Muhimatul Umami (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
The evolution of Mysticeti (baleen whales) shows a unique transition from teeth to baleen, a specialized keratin structure that allows mass filtering methods to utilize zooplankton as a primary food source. This process includes significant anatomical, morphological, and molecular changes in their evolutionary history. This study examines paleontological, ontogenetic, and molecular evidence to understand the evolutionary mechanisms of tooth loss and the emergence of baleen. Genetic analysis shows inactivating mutations in enamel genes such as MMP20, ACP4, and KLK4 that promote the loss of enamel and teeth in Mysticeti. Paleontological findings indicate proto-baleen in Aetiocetidae as an important transitional stage to modern baleen structures. This study highlights the evolution of unique adaptations in Mysticeti that enabled their ecological success as the world's largest filter-feeding predators.